Numerical simulation of flow around a pyramid using Large Eddy Simulation - Bengtsson, Anders (My University, 2014)
In this Master Thesis, flow around a pyramid with 60 apex angle at a Reynolds number of Re = 27000 was studied numerically using Large eddy simulation. The pyramid was mounted on a plate, with the base of the pyramid parallel to the plate edges. The pyramid base width was 0.045 m, and the free-stream inlet velocity was U1 = 10 m/s. Computations were performed using the software AVL Fire. The Smagorinsky model was used for the sub-grid-scale model. Simulations were compared with experiments using an identical setup which allowed for effective comparisons. A proper orthogonal decomposition was performed on the computed flow to create a set of modes to describe the flow. The computed modes were correlated to surface pressure at different locations on the pyramid surface in order to find a set of sensor location that can best be used to express the entire flow. The procedure used can then be used to find optimal measurement positions in situations where only limited measurements can be taken, such as experimental setups. It was concluded that Large Eddy Simulation can be effective in describing the flow around a pyramid, but that this requires a high spatial resolution. It was also shown that proper orthogonal decomposition can be used to identify large scale structures in the flow, as well as finding time-dependent behaviour that can be linked to surface pressures.
Keywords: Building Futures; Hållbar utveckling; Strömningsmekanik; Building Futures; Sustainable Development; Fluid mechanics